2012
DOI: 10.4314/tjpr.v11i4.19
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines Adherence and Hypertension Control in an Outpatient Cardiology Clinic in Malaysia

Abstract: Purpose: To evaluate doctors' adherence to Malaysian Clinical Practice Guideline (CPG) (Ф = 0.195, p < 0.01), p = 0.017), p = 0.017) and monotherapy (Ф = -0.168, p < 0.01

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…The total guideline adherence of doctors was 71.3% in the management of dyslipidemia along with diabetes mellitus. The results of the current study is quite similar with the study conducted in Penang General Hospital which shows adherence 67% in the cardiology ward of Penang General Hospital (Ahmad, Nafees et al, 2012). The guideline adherence of doctors on Coronary Heart Disease was about 65.6%.…”
Section: Discussionsupporting
confidence: 86%
“…The total guideline adherence of doctors was 71.3% in the management of dyslipidemia along with diabetes mellitus. The results of the current study is quite similar with the study conducted in Penang General Hospital which shows adherence 67% in the cardiology ward of Penang General Hospital (Ahmad, Nafees et al, 2012). The guideline adherence of doctors on Coronary Heart Disease was about 65.6%.…”
Section: Discussionsupporting
confidence: 86%
“…Different studies have found different levels of compliance to treatment guidelines for hypertension in various contexts. Like this study, a study conducted in Malaysia observed that doctors poorly adhered to Malaysian Clinical Practice guidelines [ 30 ]. In another study in Malaysia as well, 85.3% of prescriptions at a Cardiac clinic were in accordance with guidelines [ 31 ].…”
Section: Discussionmentioning
confidence: 89%
“…In such a scenario of severe undiagnosed hypertension in Zimbabwean population the relevance of monotherapy as observed in our study with 38% of patients being on monotherapy becomes questionable since it may not provide adequate control [ 25 , 27 ]. Indeed, in a study by Al-Drabah et al in which the majority of subjects were prescribed monotherapy, the researchers observed that target BP control was not achieved in most patients [ 29 ] which implies that monotherapy may not be sufficient for achieving adequate BP control in majority of patients [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, a study conducted in Malaysia, observed that doctors poorly adhered to Malaysian Clinical Practice Guideline (CPG) in hypertensive patients with diabetes and left ventricular hypertrophy. A better hypertension control was seen with ACEIs and guidelines-adherent therapy [ 24 ].…”
Section: Introductionmentioning
confidence: 99%